Long Terminal Repeat Retrotransposon Content in Eight Diploid Sunflower Species Inferred from Next-Generation Sequence Data - Tetreault, Hannah M.; Ungerer, Mark C. (My University, 2017)
The most abundant transposable elements (TEs) in plant genomes are Class I long terminal repeat (LTR) retrotransposons represented by superfamilies gypsy and copia. Amplification of these superfamilies directly impacts genome structure and contributes to differential patterns of genome size evolution among plant lineages. Utilizing short-read Illumina data and sequence information from a panel of Helianthus annuus (sunflower) full-length gypsy and copia elements, we explore the contribution of these sequences to genome size variation among eight diploid Helianthus species and an outgroup taxon, Phoebanthus tenuifolius. We also explore transcriptional dynamics of these elements in both leaf and bud tissue via RT-PCR. We demonstrate that most LTR retrotransposon sublineages (i.e., families) display patterns of similar genomic abundance across species. A small number of LTR retrotransposon sublineages exhibit lineage-specific amplification, particularly in the genomes of species with larger estimated nuclear DNA content. RT-PCR assays reveal that some LTR retrotransposon sublineages are transcriptionally active across all species and tissue types, whereas others display species-specific and tissue-specific expression. The species with the largest estimated genome size, H. agrestis, has experienced amplification of LTR retrotransposon sublineages, some of which have proliferated independently in other lineages in the Helianthus phylogeny.
Citation: Tetreault, H. M., & Ungerer, M. C. (2016). Long Terminal Repeat Retrotransposon Content in Eight Diploid Sunflower Species Inferred from Next-Generation Sequence Data. G3-Genes Genomes Genetics, 6(8), 2299-2308. doi:10.1534/g3.116.029082/-/DC1
Keywords: Genome Size Evolution; Helianthus; Ltr Retrotransposons; Helianthus; Agrestis; Transposable Elements